Development of a Safeguard System Using an Episomal Mammalian Artificial Chromosome for Gene and Cell Therapy - Narumi Uno; Katsuhiro Uno; Shinya Komoto; Teruhiko Suzuki; Masaharu Hiratsuka; Mitsuhiko Osaki; Yasuhiro Kazuki; Mitsuo Oshimura (Elsevier, 2015)
The development of a safeguard system to remove tumorigenic cells would allow safer clinical applications of stem cells for the treatment of patients with an intractable disease including genetic disorders. Such safeguard systems should not disrupt the host genome and should have long-term stability. Here, we attempted to develop a tumor-suppressing mammalian artificial chromosome containing a safeguard system that uses the immune rejection system against allogeneic tissue from the host. For proof-of-concept of the safeguard system, B16F10 mouse melanoma cells expressing the introduced H2-K(d) major histocompatibility complex (MHC class I)-allogenic haplotype were transplanted into recipient C57BL/6J mice expressing MHC H2-K(b). Subcutaneous implantation of B16F10 cells into C57BL/6J mice resulted in high tumorigenicity. The volume of tumors derived from B16F10 cells expressing allogenic MHC H2-K(d) was decreased significantly (P < 0.01). Suppression of MHC H2-K(d)-expressing tumors in C57BL/6J mice was enhanced by immunization with MHC H2-K(d)-expressing splenocytes (P < 0.01). These results suggest that the safeguard system is capable of suppressing tumor formation by the transplanted cells.